The Effect of the Dunn and Dunn Model in Modifying the fourth secondary class student Misconception of chemical concepts (Journal of the College of Basic Education, 2022)
The study aims to identify the effect of the Dunn and Dunn model in the modifying the fourth secondary class student misconception of the chemistry concepts. The sample of this study consists of (60) student of one of the secondary schools for gifted students in the Directorate of Education- Karkh 2 chosen intentionally. This sample has been divided into two groups, experimental and control. Each group includes (30) student. The experimental group was taught in accordance with Dunn and Dunn model whereas the control group was tough in accordance with the commonly used way of instruction. The researchers have the experimental design of partial control and a test of modifying the misconception of chemistry concepts which consists of (12) multiple-choice items. Pretest and posttest were applied and the validity and reliability were confirmed. The results show that there is a difference of statistical significance in favor of the experimental group. The researchers draw conclusions and submit recommendations and suggestion.